From Manassas to Appomattox : Memoirs of the Civil War in America - Longstreet, James (Book collections on Project MUSE., 2020)
An invaluable firsthand account of life during the Civil War, From Manassas to Appomattox, is the memior of Confederate Lieutenant General James Longstreet, the principle subordinate under General Robert E. Lee. An introduction and notes by prominent historian James I. Robertson Jr. and a new foreword by Christian Keller offer insight into the impact of Longstreet's career on American history.